Conceptualizing Spatial Heterogeneity of Urban Composition Impacts on Precipitation Within Tropics - Zakaria, Nur Hidayah; Asilah Ishak, Nur; Salleh, Siti Aekbal; Isa, Nurul Amirah; Suhana , Erniza; Gee Ooi, Maggie Chel; Abd Latif, Zulkiflee; Ustuner, Mustafa (International Journal of Sustainable Construction Engineering and Technology, 2023)
Urban composition has exacerbated precipitation patterns. Rapid urbanization with dynamic composition and anthropogenic activities lead to the change of physical environment, especially land-use and land cover which subsequently magnifies the environmental effects such as flash floods, extreme lightning, and landslides. Due to extreme and elevated temperature trends with exacerbated rainfall patterns, these environmental effects become major issues in tropics. Albeit several studies pointed out that rapid urbanization induced precipitation, studies about the heterogeneity of urban composition on precipitation variables are still limited. Thus, this paper review studies about precipitation pattern in relation to the heterogeneity of urban composition that successfully integrates geographical information system (GIS) and remote sensing techniques to enhance the understanding of interactions between precipitation patterns against heterogeneity of urban composition. This article also addressed the current state of uncertainties and scarcity of data concerning remote sensing techniques. Evidently, with a comprehensive investigation and probing of the precipitation variables in the context of urbanization models fused with remote sensing and GIS, they put forward powerful set tools for geographic cognition and understand how its influence on spatial variation. Hence, this study indicated a great research opportunity to set the course of action in determining the magnitude of spatial heterogeneity of an urban composition towards the pattern of precipitation.